KELEBIHAN DAN KELEMAHAN METODE TALAQQI DALAM PROGRAM TAHFIDZ AL-QUR’AN JUZ 29 DAN 30 PADA SISWA KELAS ATAS MADRASAH IBTIDAIYAH MUHAMMADIYAH - Ratnasari Diah Utami; Yosina Maharani (Universitas Muhammadiyah Surakarta, 2018)
The purpose of this research is to identify 1) the advantages and weakness of talaqqi method in program tahfidz Al-Qur'an juz 29,30, and 2) Attempt to overcome the weakness of talaqqi method in program tahfidz Al-Qur'an juz 29,30, The type of research used in this study is qualitative descriptive. Data collection methods used in this study are the method of observation, interview and documentation. Validity of data used is triangulation method and triangulation of data source by using three step activity data analysis that is data reduction, data presentation, and conclusion. The results of this study indicate that 1) The advantages of talaqqi method is the motivation factor and habalan memorization of students which is still less so this method is considered very suitable and effective to be applied in the madrasah and students can read and memorize the Qur'an in accordance with the rules of science that tajwid correct. The weakness of the talaqqi method is derived from its own student factors that have not mastered the science of tajwid well such as short length, pronunciation makhraj, students who are easily bored so it will be joking with friends of their own. 2) Efforts made by teachers in overcoming the weaknesses of talaqqi method is to check the reading, control the development of memorization of students, listened one by one, come to the desk students who felt still have difficulty in memorizing, and by forming homogeneous classes tailored to the level of students' memorization skills.